Large Sample Size Fallacy in Trials About Antipsychotics for Neuropsychiatric Symptoms in Dementia - Hulshof, Tessa A.; Zuidema, Sytse U.; Janus, Sarah I. M.; Luijendijk, Hendrika J. (Frontiers in Pharmacology, 2020)
Background: Atypical antipsychotics for neuropsychiatric symptoms in dementia have been tested in much larger trials than the older conventional drugs. The advantage of larger sample sizes is that negative findings become less likely and the effect estimates more precise. However, as sample sizes increase, the trials also get more expensive and time consuming while exposing more patients to drugs with unknown safety profiles. Moreover, a large sample size might yield a statistically significant effect that is not necessarily clinically relevant. Objective: To assess (1) the variation in sample size and sample size calculations of antipsychotic trials in dementia, (2) the size of reported treatment effects and related statistical significance, and (3) general study characteristics that might be related to sample size. Study Design and Setting: We performed a meta-epidemiological study of randomized trials that tested antipsychotics for neuropsychiatric symptoms in dementia. The trials compared conventional or atypical antipsychotics with placebo or another antipsychotic. Two reviewers independently extracted sample size, sample size calculations, reported treatment effects with p-values, and general study characteristics (drug type, trial duration, type of funding). We calculated a reference sample size of 83 and 433 per study group for the placebo-controlled and head-to-head trials respectively. Results: We identified 33 placebo-controlled trials, and 18 head-to-head trials. Only 14 (42%) and 2 (11%) respectively reported a sample size calculation. The average sample size per arm was 34 (range 6-179) in placebo-controlled trials testing conventional drugs, 107 (8-237) in such trials testing atypical drugs, and 104 (95-115) in such trials testing both drug types; it was 31 (10-88) in head-to-head trials. Thirteen out of 18 trials with sample sizes larger than required (72%) reported a statistically significant treatment effect, of which two (15%) were clinically relevant. None of the head-to-head trials reported a statistically significant treatment effect, even though some suggested non-inferiority. In placebo-controlled trials of atypical drugs, longer trial duration (>6 weeks) and commercial funding were associated with higher sample size. Conclusion: Sample size calculations were poorly reported in antipsychotic trials for dementia. Placebo-controlled trials of atypical antipsychotics showed large sample size fallacy while head-to-head trials were massively underpowered.